2017
DOI: 10.1021/acs.iecr.7b01473
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformed PtFe Nanocomposites Show Enhanced Catalytic Performances in Oxidation of Glycerol to Tartronic Acid

Abstract: Phase transformation in anisotropic nanocrystals is critical for enhanced surface properties of bimetallic catalysts. In this work, we report a series of phase transformed PtFe nanocomposites as catalysts for facile oxidation of glycerol to value-added tartronic acid at mild operating conditions. The lattice mismatch between Pt and Fe intrinsically drives structure reconstruction from face centered cubic (fcc) to ordered and lattice distorted face centered tetragonal (fct) phase. Surface characterization revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
(87 reference statements)
0
27
0
Order By: Relevance
“…Also, the HPLC results displayed in Figure 8c,d [36] show that the percentage of each side product remains the same throughout the electrooxidation, showing that no significant amount of any side product is further oxidized into other side products. Similarly, as shown in Figure 8d (PtFe composites oxidizing glycerol towards tartronic acid under alkaline conditions [136] ), the rapid conversion from glycerate into tartronate and other side products occurs only after the complete depletion of glycerol. This strongly supports the fact that C3 intermediates can be oxidized into other highly oxidized products, but only in the absence of glycerol.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Also, the HPLC results displayed in Figure 8c,d [36] show that the percentage of each side product remains the same throughout the electrooxidation, showing that no significant amount of any side product is further oxidized into other side products. Similarly, as shown in Figure 8d (PtFe composites oxidizing glycerol towards tartronic acid under alkaline conditions [136] ), the rapid conversion from glycerate into tartronate and other side products occurs only after the complete depletion of glycerol. This strongly supports the fact that C3 intermediates can be oxidized into other highly oxidized products, but only in the absence of glycerol.…”
Section: Discussionmentioning
confidence: 53%
“…This section summarizes the achievements and also controversies with respect to the performances of metallic catalysts reported so far. As Martins et al [136] . have commented, the properties of electrocatalysts used for GEOR are subject to preparation processes which vary significantly between studies and between groups who conduct them.…”
Section: Electrocatalysts For Enhanced Efficiency and Selectivity Of mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that thermal annealing process forces phase transformation of disordered structures to thermodynamically stable ones. In the case of PtFe system, preliminary work has shown that phase transformation from face centered cubic ( fcc ) and face centered tetragonal ( fct ) causes significant enhancement in magnetic properties (Figure ) . However, little has been known on how phase transformation influences surface electron reconfiguration and catalytic activity.…”
Section: Figurementioning
confidence: 99%
“…120 The results of high current density, excellent durability, and good CO poisoning tolerance made the addition of Fe into noble metal alloy a suitable potential for alcohol electrooxidation. 121 Jin et al 122,123 reported on the observation of interdiffused fct Pt-Fe nanocrystals that exhibited threefold higher activity than fcc Pt-Fe catalysts. Fe near Pt atoms in fct structure believed to decrease the binding energy between Pt surface and C O groups, which assisted surface to molecules oxygen transfer.…”
Section: Development Of Pt-based and Pd-based Catalyst With Iron Metalmentioning
confidence: 99%